Public Universities and Budget Cuts in Malaysia - Abdullah, Doria (International Higher Education, 2017)
Malaysian public universities have experienced drastic budget cuts over the past two years, which did not bode well for Malaysia’s academic community. This article presents an overview of the situation, explaining the rationales behind the budget cuts, adjustments made by public universities, and unaddressed gaps.